FOREST NUTRITION MANAGEMENT - Cui, Quan (DELVE Publishing, 2020)
Forest Nutrition Management examines the evaluation of forest nutrition and their management. It also includes forest ecosystem services derived by smallholder farmers in northwestern Madagascar and the change of soil carbon stock due to edge effects in central amazon forest fragments. This book also discussed about The Impact of Forest Management Plans on Trees and Carbon: Modeling A Decade of Harvesting Data in Cameroon, Modeling Micro-Scale Ecological Processes and Emergent Patterns of Mountain Pine Beetle Epidemics, Lidar-Based Estimation of Bole Biomass For Precision Management of An Amazonian Forest, Sources and Types of Uncertainties in the Information On Forest-Related Ecosystem Services and Capturing Complexity: Forests, Decision-Making and Climate Change Mitigation Action.